Left-sided primary cardiac lymphoma: a case report - Valentina Scheggi; Carlotta Mazzoni; Tiziano Mariani; Pier Luigi Stefàno (SpringerOpen, 2020)
Abstract Background Primary cardiac lymphoma (PCL) is a rare neoplasm, defined as lymphoma with the main bulk localized in the heart; diffuse large B cell lymphoma (DLBCL) is the most common type. It usually involves the pericardium and the right heart and has a poor prognosis with a median survival of less than 1 year. Case presentation A 62-year-old female presented to the emergency department for palpitations and recent-onset dyspnea. The echocardiogram showed a round-shaped mass (33 x 32 mm) in the left atrium, a mild circumferential pericardial effusion, and a hyperechogenic mass at the level of the atrio-ventricular junction. A thoracic CT scan demonstrated the presence of a bulky mediastinal mass, strictly attached to the left heart and infiltrating its posterior wall, the left pulmonary veins, and the inferior lobar bronchus. The patient underwent CT-guided biopsy, and the diagnosis of double-expressor DLBCL was made. Given the potential risk of heart rupture during chemotherapy, the first cycle of R-CHOP was performed in an in-hospital setting, with initial benefit. After completing 6 cycles of R-CHOP, imaging studies showed rapid progression of the disease; the patient was started on the salvation protocol R-DHAOX but died of septic shock 10 months later. Conclusions PCL is rare and accounts for less than 2% of primary cardiac tumors; double-expressor DLBCL carries a poor prognosis. As in most cases, the diagnosis was made after the onset of nonspecific symptoms (dyspnea) but-despite the strong predilection for right heart involvement reported in literature-our patient had a predominant left atrial infiltration.